Hereditary hemorrhagic telangiectasia diagnosed by enteroscopy: a case report - Margarita Rey; Johana Milena Salazar; Drixie Dalyla Leal; Fernando Sierra; Erika Pérez; Jose De la Hoz; Gustavo Adolfo Reyes; Mariana Vásquez Roldán (Journal of International Medical Research, 2021)
Hereditary hemorrhagic telangiectasia (HHT) is a very rare autosomal dominant multisystemic disease. Patients with this disease usually present with punctate mucocutaneous telangiectasias and arteriovenous malformations. The diagnostic criteria currently in use are the Curaçao criteria. HHT is considered a clinical diagnosis; thus, no imaging or preclinical laboratory is mandatory, and diagnosis and management are performed according to the experience of the treating team. We herein describe a 58-year-old man with no significant medical history who presented with a 15-day history of intermittent hematochezia. He was admitted to the hospital and underwent a series of laboratory tests, including colonoscopy, which showed normal results. Therefore, the patient was discharged with a diagnosis of gastrointestinal bleeding. During his second visit to the emergency room, the doctors requested video capsule endoscopy because of the patient’s history, and a diagnosis of HHT was made. The entire approach and treatment were completed with antegrade double-balloon enteroscopy. This case highlights the importance of endoscopic methods for timely diagnosis and proper management.